2013
DOI: 10.1177/1535370213498978
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of HIF-1α in pulmonary fibrosis induced by paraquat

Abstract: It is commonly accepted that epithelial-mesenchymal transition contributes to fibrotic remodeling, but the molecular pathways involved in paraquat (PQ)-induced epithelial-mesenchymal transition remain uncharacterized. The objective of this study was to evaluate the potential involvement of HIF-1α in TGF-β1/β-Catenin and Snail pathway after PQ poisoning. In our study, 86 Spragne-Dawley rats were randomly divided into control group and PQ group, which received intragastric infusion of 20% PQ solution 50 mg/kg. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…Transforming growth factor-b1 is a classical EMT-promoting cytokine, and many studies have shown the relationship between HIF-1a and TGF-b1 in the process of EMT [13,35,36]. We also found that TGF-b1 has a positive correlation with HIF-1a as well as Snail and b-catenin in PQ poisoning-induced pulmonary fibrosis, the latter of which are the two other EMT-promoting cytokines in addition to TGF-b1 [26]. To further investigate the interaction among HIF-1a, Snail and b-catenin, we measured the expression changes of Snail and b-catenin by Western blotting after silencing HIF-1a expression in vitro.…”
Section: Hif-1a May Regulate Emt Via the Snail And B-catenin Pathwayssupporting
confidence: 63%
See 1 more Smart Citation
“…Transforming growth factor-b1 is a classical EMT-promoting cytokine, and many studies have shown the relationship between HIF-1a and TGF-b1 in the process of EMT [13,35,36]. We also found that TGF-b1 has a positive correlation with HIF-1a as well as Snail and b-catenin in PQ poisoning-induced pulmonary fibrosis, the latter of which are the two other EMT-promoting cytokines in addition to TGF-b1 [26]. To further investigate the interaction among HIF-1a, Snail and b-catenin, we measured the expression changes of Snail and b-catenin by Western blotting after silencing HIF-1a expression in vitro.…”
Section: Hif-1a May Regulate Emt Via the Snail And B-catenin Pathwayssupporting
confidence: 63%
“…The regulation of HIF-1a in EMT is partly modulated by Snail and b-catenin in cancer [24,25]. In our previous research, we found a positive correlation among HIF-1a, Snail and b-catenin after PQ poisoning [26]. However, the relationship among HIF-1a, Snail and b-catenin has not been extensively researched in pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 87%
“…It is reported that PQ induces EMT during pulmonary fibrosis in vitro and in vivo 13, 28 . In our study, we also observed EMT-like phenotypic changes in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that HIF-1a and epigenetics likely to form a network signaling pathway. addition, Xie et al suggested that HIF-1a may cooperate with TGFb1/b-Catenin signaling pathway and play a role as cross linking agency in pulmonary fibrosis [76]. Furthermore, it has been well demonstrated that NF-kB signaling pathway plays an important role in the regulation of HIF-1a [77].…”
Section: Others Pathwaysmentioning
confidence: 98%